Household dependence on solid cooking fuels in Peru: An analysis of environmental and socioeconomic conditions. (September 2019) - McLean, Elena V.; Bagchi-Sen, Sharmistha; Atkinson, John D.; Schindel, Alexandra
Highlights: Solid fuel dependence is lower in Peru's non-coastal regions and the capital. Elevation, forest cover, rural population and poverty increase regions' solid fuel use. Female literacy, mobile and electricity access reduce solid fuel dependence. In contrast to skilled occupations, female employment in domestic jobs boosts solid fuel use. Areas with significant indigenous populations have greater solid fuel dependence. Abstract: Solid fuel use is linked with adverse effects on the environment and human health. Yet, solid fuels remain an important energy source for households in developing countries. Even when country-level dependence on solid fuels is modest, there is often significant variation in within-country patterns of solid fuel use. This study examines a range of environmental and socioeconomic conditions to understand the relationship between them and household energy use within a country. While our results are derived from a study of regional patterns of solid fuel dependence in Peru, the contribution of this study is broad: variables that we include in our models of households' fuel choice decisions are likely to shape such decisions in most developing countries. Our findings indicate that environmental conditions, such as elevation and forest cover, are associated with solid fuel use. Socioeconomic factors, including urbanization, poverty and female literacy, are similarly important. In addition, we identify nuanced links between types of female employment and indigenous population, on the one hand, and solid fuel use, on the other.